O estudo da ironia no conto missa do galo, de Machado de Assis - RODRIGUES, Paulo Ronaldo Nogueira (2022)
This work seeks to analyze the irony in the short story Missa do Galo, by Machado Assis. Therefore, the research was materialized through a bibliographic nature with the reading of the short story “Missa do Galo”, by Machado de Assis and, later, with the reading of works by authors of Literature such as Moisés (1960), Guimarães (1988), Oliveira (2011), França (2008), Spalding (2008), Perrot (2008), Gotlib (1990), Marins (2004), Santos (2010), Machado (2014), Dante (2013), which approach the tale and the figure of speech irony within the theme. It is noteworthy that Machado's irony is present in several of the author's short stories, but for the sake of research delimitation, we chose to work with the short story Missa do Galo due to the characteristics of fine irony and the power of the figure to reach the reader's thought. giving the plot a touch of plurisignification and multiple hypotheses for analysis. At this juncture, irony traced the meaning of concealing a sensual game between the characters and, at the same time, softening the entire situation and contexts of the tale in its psychological field.